Screening program for hepatitis c virus in an open population at a third-level healthcare center - F Higuera-de la Tijera; E Rodríguez-Fuentes; ML Hernández-Medel; JL Pérez-Hernández; R Serrano-Loyola; GML Guerrero-Avendaño (Annals of Hepatology, 2022)
Introduction and Objective: Worldwide, there are 71 million people with chronic hepatitis C (HCV), and yearly 1,5 million become infected. In Mexico, it is estimated between 400,000 to 600,000 viremic. Among the WHO goals for 2030 is to detect >90% of people with HCV. This study aimed to describe the screening strategy carried out in the open population using two-step HCV screening tests at the Hospital General de México from January to December 2021. Materials and Methods: Study in an open population that attended the General Hospital of Mexico for any reason, and agreed to take the risk factor questionnaire and underwent a rapid test for the detection of anti-HCV antibodies (RT), which were reactive, load viral (PCR to detect HCV-RNA). Descriptive statistics and the statistical package STATA v.14 were used. Results: In 2021, 33,523 subjects were examined; 71.5% were women, mean age of 47±10 years. Reported at least one risk factor for HCV 53.5%. The most frequent risk factors were: Multiple sexual partners/history of sexually transmitted diseases (STDs) 36.2%, tattoos/piercings 26.7%, surgery before 1995 20.2%, transfusion before 1994 5.4 % and health workers after accidental puncture 4.2%. Of the 33,523, 0.7% were reactive in RT. Of the reagents in RP, the PCR was positive in 57.9% (prevalence of viremia= 0.4%). Of the viremic patients, the risk factors identified were blood transfusion before 1995 37%, multiple sexual partners/STDs 35%, surgery before 1995 30%, tattoos/piercings 30%, and injected drugs only 3.5%. All viraemic (100%) linked to treatment. Conclusions: HCV prevalence was similar to that previously reported. Traditional risk factors such as transfusion or surgery remain highly prevalent. Timely diagnosis of HCV allows linkage to treatment. Funding: The resources used in this study were from the hospital without any additional financing Declaration of interest: The authors declare no potential conflicts of interest.